Sustainability practices among Indonesian oil palm smallholders - Shella Vidya Pandiangan; Ernah Ernah (Center for Science and Technology, IAIN Surakarta, 2019)
Indonesia is the largest oil palm producing country in the world. The increases of plantation area and oil palm production in Indonesia are feared to have negative impacts on environment. As an effort to overcome it, Indonesian Government made a certification called Indonesian Sustainable Palm Oil (ISPO). This research was carried out in plasma plantations in Siak Regency, Riau, Indonesia. The purpose of this study is to determine characteristics of smallholders and application of sustainability aspects in facing ISPO standardization. Results showed that average sample of smallholders who was men, in their productive age, had received 9-year compulsory education program, and had more than 10-year farming experience. Application of economic aspect is in